Linguistic Relativism and the Expression of Basic Theoretical Rationality in Inuktitut - Mahieu, Marc-Antoine (Études Inuit Studies)

(untitled) (Centre interuniversitaire d’études et de recherches autochtones (CIÉRA), 2022)
This paper begins by stressing the importance of distinguishing between linguistic relativity, whose reality is hardly debatable, and linguistic relativism, which ultimately holds that language communities are locked within their own worldview, hence their own notions of truth. It then rejects linguistic relativism by asserting the existence of a universal core of theoretical rationality comprised at the very least of the logical principles of identity, noncontradiction, and excluded middle. It goes on to show how this theoretical rationality manifests itself in the lexicon of a language that differs greatly from English: Inuktitut spoken by Inuit of Nunavik (Arctic Quebec). The definitions provided by Taamusi Qumaq for three words relating to critical thought are translated for the first time. Other quotes give examples of theoretical rationality in actual usage. Finally, the paper asks why logic as such is accorded little value in the culture Inuktitut expresses. The suggested answer follows Jack Goody, who holds that a long written tradition is required for the rules of formal logic to take hold in language practices. Writing is not just a transcription of the spoken word; it is an intellectual technology that impacts the way speakers use their language.